From Curriculum to Construction: Mapping a Landscape of Transdisciplinary Practice in European Architecture and beyond - Jany, Andrea (Technium: Romanian Journal of Applied Sciences and Technology, 2025)
This study explores how transdisciplinary approaches in architectural education manifest in built outcomes at the building scale in Europe. Using a structured set of 13 case studies across three typologies - Transdisciplinary Learning Laboratories, Participatory Housing & Community Prototypes, and Circular Design & Educational Studios - it maps the trajectory from curriculum-based pedagogies to real-world construction. Through comparative analysis, this study reveals patterns in knowledge co-production, stakeholder integration, and spatial realization. Key findings include the emergence of a curriculum-construction continuum, where student learning extends from conceptualization to implementation. In addition, the redefinition of students’ roles as co-researchers and mediators across institutional boundaries and the importance of long-term partnerships between academia, municipalities, and industry. Furthermore, challenges in aligning academic timelines with construction processes and sustaining stakeholder engagement necessitate flexible regulatory mechanisms and new evaluation metrics for transdisciplinary work. This study contributes to ongoing debates in architectural education by demonstrating how transdisciplinary logic can be operationalized from curriculum to construction. It argues for a paradigm shift in architectural pedagogy towards more socially engaged, ecologically literate, and epistemologically reflexive approaches. The paper concludes by outlining future research directions, including longitudinal impact studies and the development of meta-analytical tools for assessing transdisciplinary studios’ effectiveness. Using a structured set of case studies, it maps the trajectory from curriculum-based pedagogies to real-world construction, categorized into three typologies: learning laboratories, participatory housing, and circular design studios. Through comparative analysis, this study reveals patterns in knowledge co-production, stakeholder integration, and spatial realization, offering a conceptual and empirical contribution to the discourse on transdisciplinary architecture.